2017
DOI: 10.1016/j.redox.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Redox imbalance and mitochondrial abnormalities in the diabetic lung

Abstract: Although the lung is one of the least studied organs in diabetes, increasing evidence indicates that it is an inevitable target of diabetic complications. Nevertheless, the underlying biochemical mechanisms of lung injury in diabetes remain largely unexplored. Given that redox imbalance, oxidative stress, and mitochondrial dysfunction have been implicated in diabetic tissue injury, we set out to investigate mechanisms of lung injury in diabetes. The objective of this study was to evaluate NADH/NAD+ redox statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 99 publications
2
48
1
Order By: Relevance
“…As glucose flux through the polyol pathway consumes NADPH, it has been suggested that the level of NADPH could be significantly decreased . Indeed, we have found that this is the case in diabetic lung and pancreas, whereby NADPH content is lower than that in controls. It has been established that there is about a 15% decrease in NADPH in the diabetic lens .…”
Section: The Polyol Pathwaymentioning
confidence: 56%
See 2 more Smart Citations
“…As glucose flux through the polyol pathway consumes NADPH, it has been suggested that the level of NADPH could be significantly decreased . Indeed, we have found that this is the case in diabetic lung and pancreas, whereby NADPH content is lower than that in controls. It has been established that there is about a 15% decrease in NADPH in the diabetic lens .…”
Section: The Polyol Pathwaymentioning
confidence: 56%
“…So when NAD + levels decrease during diabetes, sirtuin activities will be decreased, and this can also be modulated by decreased expression of sirtuin proteins. Indeed, numerous studies including ours, have demonstrated attenuated expression of sirtuin proteins in diabetes . As a consequence, protein acetylation is increased (Figure A), leading to functional changes of numerous proteins .…”
Section: The Polyol Pathwaymentioning
confidence: 72%
See 1 more Smart Citation
“…12 ROS produced primarily in the mitochondria as a byproduct of metabolism, and mitochondria are also a vulnerable target of ROS-induced oxidative damage. 28,34 Meanwhile, other reports also showed that ROS mediates oxidative damage that may lead to mitochondrial dysfunction in mammalian oocytes. 34,35 Particularly, mammalian oocytes are very sensitive to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…ATP content was measured spectrophotometrically by an ATP probe kit that was purchased from BioVision (Milpitas, CA, catalog# K354–100). This assay employs phosphorylation of glycerol by ATP to yield ADP, and the byproduct of this reaction eventually oxidizes the probe to form resorufin that can be easily monitored at 570 nm [65, 66]. Mitochondrial function measured as mitochondrial respiration was performed using Mito-ID extracellular oxygen sensor kit as previously described [67].…”
Section: Methodsmentioning
confidence: 99%